Participation in road cycling vs running is associated with lower bone mineral density in men - Rector, R. S.; Rogers, R.; Ruebel, M.; Hinton, P. S. (Metabolism, 2008)
The effects of regular non-weight-bearing (NWB) exercise on bone health are largely unknown. The objective of the study was to determine the effects of participation in NWB sports on bone health in adult male recreational athletes. Male cyclists (NWB; n = 27) and runners (weight-bearing [WB]; n = 16) aged 20 to 59 years were recruited from the community. Whole-body and regional bone mineral content and bone mineral density (BMD), and body composition were assessed using dual x-ray absorptiometry. Bone formation and resorption markers, and hormones were measured in serum. Bone-loading history was estimated from a sports participation history questionnaire. Nutrient intake and current physical activity were estimated from 7-day written logs. The NWB athletes had significantly lower BMD of the whole body and spine than the WB athletes, despite having similar age, weight, body mass index, body composition, hormonal status, current activity level, and nutrient intakes. Sixty-three percent of NWB athletes had osteopenia of the spine or hip, compared with 19% of WB athletes. Cyclists were 7 times more likely to have osteopenia of the spine than runners, controlling for age, body weight, and bone-loading history. There were no group differences in serum markers of bone turnover. Based on the results of this study, current bone loading is an important determinant of whole-body and lumbar spine BMD. Therefore, bone-loading activity should be sustained during adulthood to maintain bone mass.